Game perception in primary school teachers (Isparta example) - Abdullah Yavuz Akinci; Mehmet Yildirim (Revista on line de Política e Gestão Educacional)
The aim of this research is to reveal the attitudes of primary school teachers about the participation of primary school students in the game, how the classroom teachers perceive the game, how they interpret the relationship between the game and the child, and how they evaluate the game in line with the curriculum. In the 2020-2021 academic year, 343 primary school teachers selected randomly among 1230 primary school teachers working in primary schools affiliated to the Isparta Provincial Directorate of National Education participated in the study. Google Forms platform was used for data collection. This method has been preferred to maintain social distance during the pandemic process. As a result, it has been understood that teachers have an important role in the students' ability to benefit from the game sufficiently, and it is thought that the differences seen in the sub-dimensions are due to the differences in the nature of the information, its origin and accuracy, understanding and evaluation, change, and the perceptions of the teachers in the processes of producing and acquiring information.